Research on the Influence of Calligraphy Education on College Students’ Cultural Identity - Xu, Yating (Journal of Educational Research and Policies, 2025)
This study takes the role of calligraphy education in enhancing college students’ cultural identity as the research object, aiming to explore in depth the impact of calligraphy education on the cultivation of college students’ cultural identity. Through analysis and research, the importance and necessity of calligraphy education in universities in the current educational background are revealed. Starting from the importance of cultural identity, this paper explores the connotations of cultural identity. Then, the importance and role of calligraphy education in promoting cultural identity among college students are discussed. Finally, by studying the role and path of calligraphy education in cultivating students’ moral character, traditional cultural values, aesthetic taste, and emotions, this article discusses the cultivation of students’ ideological and moral qualities. Finally, feasible methods for enhancing cultural identity among college students through calligraphy education in universities, including curriculum design and implementation, faculty building and teaching resource guarantees, and evaluation and improvement mechanisms, should be explored. The aim of this study was to provide theoretical support and practical guidance for calligraphy education in universities to enhance the cultural identity of college students.